Preparation, spectroscopic studies and X-ray structure of homobinuclear lanthanide(III) complexes derived from 2,6-diformyl-4-chlorophénol-bis-(2’-hydroxy-benzoylhydrazone) - Pepe Marcel Haba (Bulletin of the Chemical Society of Ethiopia, 2006)
Reaction of the 2,6-diformyl-4-chlorophenol-bis-(2'-hydroxy-benzoylhydrazone) with Ln(NO3)3.nH2O (n = 5 or 6 and Ln = Y, La, Ce, Pr, Nd, Sm, Gd, Dy, Er and Yb) produces homobinuclear complexes. These complexes have been characterized by analysis, molar conductance, magnetic measurements, infrared spectral studies and X-ray diffraction. The analytical data showed 1:3 (metal:ligand) stoichiometry. Molar conductance measurements in dmf indicate 1:3 electrolytes in all cases. Magnetic moment values are close proximity of the Van Vleck values. IR studies suggest the coordination of the ligand is through the azomethine, the phenolic oxygen atom and the carbonyl oxygen of the hydrazonic moiety. The nitrate ion is also found to be ionic in all the complexes. An X-ray structure determination of [C66H48N12O15Cl3Er2]Cl2NO3.5H2O confirms the conclusion from the spectroscopic studies and show that the erbium is at the centre of a tricapped trigonal prism with coordination number nine. In all the complexes the lanthanide ions have substantially similar coordination.